Upaya Meningkatkan Kemampuan Mengenal Koperasi Dalam Meningkatkan Kesejahteraan Keluarga Melalui Metode Picture And Picture Pada SD Negeri 023 Pandau Jaya - RISNAWATI, RISNAWATI (Jurnal Daya Saing, 2017)
Abstract: Social Lessons for elementary school students need a lot of methods in order to achieve effectiveness pembelejarannya. As in the social studies teachers need to implement a variety of methods. Case at 023 elementary schools Pandau Jaya require attention and of the study of literature allegedly using picture and picture can improve student understanding. Using action research method and samples of primary school and analyzed descriptively. The results showed that the portrait IPS learning already achieved the expected objective teacher performance indicators set out in> 85% of the number of students in a class have achieved mastery learning individually. There is a learning outcome IPS particularly in sub discussion of cooperatives in improving the welfare of the community, through teaching methods picture and picture already improving student understanding. Keywords: Ability to know Cooperative, Methods Picture and Picture